(untitled) (Italian Journal of Public Health, 2010)
Background: The burden of injuries and disabilities in Pakistan is significant. Our study attempted to describe the circumstances, risk groups, types and severity of injuries experienced by patients attending a tertiary care hospital in Karachi, Pakistan. Methods: A retrospective study was conducted in the department of Emergency Medicine (ED) at Aga Khan University Hospital of Karachi, Pakistan. Past medical records from June 2006 till May 2007 of injured patients presented to ED were reviewed. Data were recorded regarding the basic epidemiological features, hospital stay, body parts injured and severity of injuries. Results: A total of 631 patients with injuries were identified. The majority of them were males (80%; n=502), aged 21-40 years (63%). Road traffic injuries (RTIs) 65% (n=411) followed by gunshots (14%, n=85) were the most common types of injuries. Upon arrival to hospital 82% (491/598) of patients had a Glasgow Coma Scale (GCS) ≥13. The mean hospital stay and Injury Severity Score (ISS) of patients were 3.5 days (SD ±6.4) and 4 (SD ±5.2) respectively. The head, neck and face were the most affected body parts (50%; n=276). Three percent (n=17) were pronounced dead on arrival to the ED. Among RTIs, multivariable logistic regression identified sex (aOR: 3.797; 95% CI: 1.066–13.528), and mode of travel (aOR: 2.883; 95%CI: 1.330–6.250) as independent predictors for severe GCS (GCS<8). Conclusions: RTIs were the most common type of injuries, common among young males. In RTIs, children were mostly pedestrians, and females and motor vehicle occupants were more likely to have severe GCS. This study may assist local authorities in Karachi to prioritize interventions to address common injuries in those who are high at risk.